Anti-Tumour Potentials of Methanol Extracts of Allium sativum on Serum IL-10, and IFN-ã in 7,12 Dimethyl Benzene-(a)-Anthracene Breast Tumour-Induced Albino Rats - Alhassan Hussaini Mohammed, Mohammed Haruna Yeldu, Usman Musa, Usman Malami Aliyu, Safiya Yusuf, Isiyaku Adamu, Isiyaku Abdullahi and Hamisu Abdullahi (Sokoto Journal of Medical Laboratory Science)
Breast cancer is an uncontrolled cell proliferation, leading to tumor formation, in this case tumor may grow in different breast areas, such as lobules, ducts, and connective tissue. The hallmark of cancer pathology is not the tumor itself, but the migration of transformed cells to different tissues. Presently, there is no known curative anti-cancer/tumor drugs. The aim of this research is to evaluate the effects of Garlic on serum level of IL-10 and IFN-ã in 7,12 Dimethyl Benzene-(a)-Anthracene Breast tumor-induced albino rats . Fresh garlic bulbs were identified/authenticated and subjected to Methanolic extractions. The total of 24 rats were grouped into 6 groups of 4 rats each. These groups are: The normal and positive controls, Acetylsalicylic acids, preventive, and treated group and synergistic group. All the groups were inducted with 65 mg/kg- 1 b.w. of 7,12 Dimethylbenzene-(a)-anthracene with the exception of Group I, and observed for 14 days, before treatment with 100mg of ASA (III), and Allium sativum (IV, V, VI). Rats were killed by surgical dislocation, 24hrs of the last treatment, the blood, were collected for ELISA evaluation and assessment. After the treatment with Allium sativum extracts and ASA in all the respective groups, the serum IL-10, was up-regulated while the IFN-ã was significantly down-regulated, when compared with the positive controls (P≤ 0.05) . The extract was found to also exhibit chemoprotective activities in group IV, where the level of IFN-ã and IL-10, remained absolutely within the normal range, when compared with group I, despite being induced with carcenogen. The research indicated that the ethanolic extracts of A. sativum may possess an a n t i - t u m o r, i m m u n o s u p p r e s s i v e a n d immunomodulatory effects, it may be use in th treatment of breast cancer patients.